2019
DOI: 10.26508/lsa.201800218
|View full text |Cite
|
Sign up to set email alerts
|

Location-dependent maintenance of intrinsic susceptibility to mTORC1-driven tumorigenesis

Abstract: Neural stem/progenitor cells (NSPCs) of the ventricular–subventricular zone (V-SVZ) are candidate cells of origin for many brain tumors. However, whether NSPCs in different locations within the V-SVZ differ in susceptibility to tumorigenic mutations is unknown. Here, single-cell measurements of signal transduction intermediates in the mechanistic target of rapamycin complex 1 (mTORC1) pathway reveal that ventral NSPCs have higher levels of signaling than dorsal NSPCs. These features are linked with differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Tsc2 deletion causes more severe phenotypes than Tsc1 in mice, but have only recently been performed in embryonic NSCs and GFAP positive postnatal astrocytes (Way et al, 2009 ; Zeng et al, 2011 ; Mietzsch et al, 2013 ; Moon et al, 2015 ). Recently, a group demonstrated that TSC patient tubers stain positive for excitatory NSC forebrain markers, that SEGAs stain positive for inhibitory NSC markers, and that inhibitory NSC Tsc2 deletion generates lesions recapitulating SENs (Rushing et al, 2019 ).…”
Section: Tsc Sega-genesismentioning
confidence: 99%
“…Tsc2 deletion causes more severe phenotypes than Tsc1 in mice, but have only recently been performed in embryonic NSCs and GFAP positive postnatal astrocytes (Way et al, 2009 ; Zeng et al, 2011 ; Mietzsch et al, 2013 ; Moon et al, 2015 ). Recently, a group demonstrated that TSC patient tubers stain positive for excitatory NSC forebrain markers, that SEGAs stain positive for inhibitory NSC markers, and that inhibitory NSC Tsc2 deletion generates lesions recapitulating SENs (Rushing et al, 2019 ).…”
Section: Tsc Sega-genesismentioning
confidence: 99%
“…Recent work using single cell gene expression has described the existence of multiple cellular states in glioblastoma tumors and the ability of cells to transition between states ( Neftel et al, 2019 ). Similar to most transcript-based studies, RAPID analyses were performed on cells collected at a single timepoint, precluding a direct investigation of the ability of GNP or GPP cells to transition to other phenotypes; however, it is possible that phosphorylated, active STAT3, STAT5, and S6 may enable transition between progenitor-like states as they do in earlier development, and thus influence patient outcome ( Rushing et al, 2019 ; Yoshimatsu et al, 2006 ). Another key research question for the future will be whether the signature features of the risk stratifying cells seen here will also be seen in other types of intractable human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Controversial studies have investigated this SVZ niche as a region originating glioma stem cells [36,37]. Among those publications, signaling via mTORC1 (mammalian target of rapamycin complex 1), protein activating HIF-1α, has been proposed to regulate self-renewal, proliferative divisions, differentiation, and brain ventricle morphogenesis in this SVZ [38]. HIF-1α was also described as a repressor of BMP (Bone Morphogenetic protein) and thus, promoting HGG precursors in the SVZ niche [21].…”
Section: Role Of Brain Physiological Hypoxia Location or Brain Physiomentioning
confidence: 99%
“…This can also explain why a really frequent invasive terminal process in this SVZ is present during pHGG progression. It results from mTor/HIF-1α expression in the tumors and its close hypoxic environment [13,38,44].…”
Section: Role Of Brain Physiological Hypoxia Location or Brain Physiomentioning
confidence: 99%
See 1 more Smart Citation